Al-Jam’iyatul Al-Washliyah Educational Institutions (1930-2000): Existence, Typology of Education, and Its Issues - Nisa, Khairun; Ansori, M Afif; Andari, An An; Kholil, Muhamad; Sudarningsih, Sudarningsih (Yupa: Historical Studies Journal, 2024)
Al-Jam'iyatul Al Washliyah is an Islamic educational institution in Indonesia founded in 1930 in Medan, North Sumatra by Haji Mohd Arsyad Al Banjari, it aimed to disseminate Islamic teachings and strengthen the identity of Muslims in Indonesia. This research employs a literature study method relying on bibliographic sources from recent journal articles and books related to the core issues and data interpretation through expert insights with a constructive approach and content analysis interpretation. The scope of the study encompasses the period from the establishment of Al Washliyah in 1930 until the end of the 20th century, specifically the year 2000. Al Washliyah was established during the Dutch colonial period to unite Muslims and advocate for Indonesian independence. They demonstrated a high commitment to education by establishing schools and madrasas and forming the Education, Teaching, and Cultural Council. During the 14th Al Washliyah Congress, they formulated educational development plans focusing on household education, madrasa/higher education, and community education. The Al Washliyah management was dedicated to education, having its curriculum for madrasas.